Sustained Pain-Related Depression of Behavior: Effects of Intraplantar Formalin and Complete Freund's Adjuvant on Intracranial Self-Stimulation (ICSS) and Endogenous kappa Opioid Biomarkers in Rats. (23rd September 2014) - Leitl, Michael D; Potter, David N; Cheng, Kejun; Rice, Kenner C; Carlezon, William A; Negus, S Stevens
Background: Intraplantar administration of complete Freund's adjuvant (CFA) and formalin are two noxious stimuli commonly used to produce sustained pain-related behaviors in rodents for research on neurobiology and treatment of pain. One clinically relevant manifestation of pain is depression of behavior and mood. This study compared effects of intraplantar CFA and formalin on depression of positively reinforced operant behavior in an assay of intracranial self-stimulation (ICSS) in rats. Effects of CFA and formalin on other physiological and behavioral measures, and opioid effects on formalin-induced depression of ICSS, were also examined. Results: There were four main findings. First, consistent with previous studies, both CFA and formalin produced similar paw swelling and mechanical hypersensitivity. Second, CFA produced weak and transient depression of ICSS, whereas formalin produced a more robust and sustained depression of ICSS that lasted at least 14 days. Third, formalin-induced depression of ICSS was reversed by morphine doses that did not significantly alter ICSS in saline-treated rats, suggesting that formalin effects on ICSS can be interpreted as an example of pain-related and analgesic-reversible depression of behavior. Finally, formalin-induced depression of ICSS was not associated with changes in central biomarkers for activation of endogenous kappa opioid systems, which have been implicated in depressive-like states in rodents, nor was it blocked by the kappa antagonist norbinaltorphimine. Conclusions: These results suggest differential efficacy of sustained pain stimuli to depress brain reward function in rats as assessed with ICSS. Formalin-induced depression of ICSS does not appear to engage brain kappa opioid systems.